Creating Value-added Teak Products for The Elderly According to The Creative Economy Concept - Phongsathorn Kanthawong; Chaiwat Somsri; Kittiporn Sangkadis; Tungkhawat Chuagulajati; Kanniga Sawetpawit; Parichat Koonklean (PT FORMOSA CENDEKIA GLOBAL, 2023)
The objectives of this research were 1) to study the value-added model of teak wood products for the elderly among teak wood entrepreneurs, 2) to create prototypes of teak wood products for the elderly. This research is qualitative research. The sample group consisted of 30 elderly people in Don Moon Sub district, Sung Men District, chosen by purposive random sampling method. Interview form was used as the research tool used for the for data collection. The outcome was then taken to the experts in wood products to evaluate the quality. The results were analyzed by descriptive statistics, including percentage, mean and standard deviation. The results showed that 1) the elderly needed 3 types of products: (1) Walker 01/65, (2) Walker 02/65, and (3) backrest chair products. 2) Evaluation results quality from experts in wood products found that the overall quality was at the highest level. The mean was 4.27 and the standard deviation was 0.64.